Prognostic factors influencing venous patency after thrombectomy in patients with May-Thurner syndrome - Chang Hoon Oh; In Chul Nam; Doo Ri Kim; Jung Ho Won; Hyoung Nam Lee; Sung-Joon Park; Youngjong Cho (PLoS ONE, 2025)
Purpose To evaluate the prognostic significance of venographic findings and procedural factors for long-term venous patency after thrombectomy in patients with May-Thurner syndrome (MTS)-associated deep vein thrombosis (DVT). Materials and Methods This retrospective cohort study included 75 patients with iliofemoral DVT secondary to MTS, who underwent thrombectomy between January 2011 and April 2023. Key venographic findings—venous stenosis (≥50%), venous spur, and persistent collaterals—along with stent placement and diameter were analyzed. The primary outcome was 24-month venous patency, assessed using univariate tests, Kaplan–Meier survival analysis, and multivariate Cox proportional hazards modeling. Results At 24 months, 58 patients (77.3%) maintained venous patency, whereas 17 (22.7%) experienced reocclusion. Univariate and Kaplan–Meier analyses showed that stenosis ≥50%, venous spur, persistent collaterals, and absence of stent placement were significantly associated with reduced patency (all p < 0.05). However, in the multivariate Cox model, only venous stenosis ≥50% remained a statistically significant independent predictor of reocclusion (hazard ratio [HR]=5.04; 95% Confidence Interval: 1.28–19.82; p = 0.021). Stent placement (HR = 1.78; p = 0.337) and diameter ( p = 0.349) were not independently associated with patency. Conclusion Residual venous stenosis ≥50% following thrombectomy is an independent predictor of reduced long-term patency in patients with MTS. While stent placement was associated with better outcomes in the univariate analysis, it did not independently predict patency after adjustment, likely due to treatment-related confounding factors. Effective anatomical resolution of stenosis may be more critical than stent deployment. Prospective studies are warranted to clarify the prognostic impact of venographic findings and interventional strategies.